Credit ratings and bond spreads of the GIIPS. Issue 2 (22nd January 2016) - de Vries, Tim; de Haan, Jakob
Abstract: We examine the relationship between credit ratings and bond yield spreads of peripheral countries in the euro area (Greece, Ireland, Italy, Portugal and Spain) for the period 1995–2014. Since 2012, bond spreads of those countries have come down very fast, whereas credit ratings have hardly changed. Our results suggest that credit rating agencies have become more cautious and have changed their approach to assess credit risk of sovereigns, and that the impact of sovereign credit risk ratings on sovereign bond spreads has changed.